Green Intellectual Capital and Corporate Governance Influence Firm Value Through Financial Performance in LQ45 - Yenita Wahyuni; , Omi Pramiana (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
This study investigates the influence of Green Intellectual Capital and Corporate Governance toward firm value, where financial performance acts as a mediating factor. The study targets LQ45-listed companies on the Indonesia Stock Exchange from 2022 to 2024. A quantitative causal approach was applied, using purposive sampling to obtain 29 firms with a total of 87 firm-year observations. Analyses were performed using multiple linear regression and Sobel mediation methods employed, and The empirical evidence suggest that Green Intellectual Capital and Sound Corporate Governance practices exert a significant positive effect on financial performance and firm value. In addition, financial performance, proxied by ROA, positively affects firm value and plays a partial mediating role in the relationship with Green Intellectual Capital, Corporate Governance, and firm value. These findings are consistent with signaling theory (Ross, 1977), suggesting that strong green intellectual capital practices and effective corporate governance send favorable signals to investors. This study contributes to sustainable accounting literature and provides practical insights for firms and investors in enhancing firm value.